TINJAUAN ASPEK ERGONOMI LOKET PENDAFTARAN BPJS 1 GUNA MENUNJANG MUTU PELAYANAN KESEHATAN DI RSUD CIBABAT CIMAHI - Rohaeni, Neni; Rahayu, Ayu Hendrati; Pujilestari, Intan (Jurnal TEDC; Vol 15 No 1 (2021): JURNAL TEDC, 2021)
A room or space ergonomic and equipped with adequate facilities and infrastructure will create a sense of security and comfort to improve the quality of medical services in hospitals Cibabat Cimahi. As for the problems that researchers found in a field that is of a room the ergonomic, yet the distance between the officers too close thus limiting the space motion of the officers, as well as the facilities and infrastructure are not yet adequate such as the lack of number of seats currently available with the number of as many as 30 seats and a patient waiting room area that is less extensive given the large number of patients coming in each day approximately 380 patients.The research method used is descriptive research methods with quantitative approach that is a bunch of objects aims to see the description of the phenomena that occur in a specific population dealing with numbers and analysis using statistics.From the results it can be concluded that the registration counters BPJS 1 outpatient in hospital Cibabat Cimahi in ergonomic yet with broad the children are 42.38 m 2 , it is clearly visible from a distance of between attendant adjacent to the average distance such as 21.2 cm, room temperature range 32 0 C aircraft as well as the facilities and infrastructure are not yet sufficient to become supporters in the improved quality of service for the hospital.Suggestions from the author : petition for filing, smoothing files patients claim BPJS piled, sorting clerk, the addition of facilities and infrastructure, as well as the efficiency of the use of the room.